2021
DOI: 10.48550/arxiv.2105.09336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenomenology of spectral functions in disordered spin chains at infinite temperature

Lev Vidmar,
Bartosz Krajewski,
Janez Bonca
et al.

Abstract: Studies of disordered spin chains have recently experienced a renewed interest, inspired by the question to which extent the exact numerical calculations comply with the existence of a manybody localization phase transition. For the paradigmatic random field Heisenberg spin chains, many intriguing features were observed when the disorder is considerable compared to the spin interaction strength. Here we introduce a phenomenological theory that may explain some of those features. We develop a theory based on th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…We also note that recently there have been a number of papers expressing various levels of skepticism about the stability of the MBL phase in the limits of large systems and long times [44][45][46][47][48][49], and a number of challenges to those conclusions [50][51][52][53]. While our results do not support (nor directly contradict) any of these arguments against the existence of the MBL phase, our work was, in part, motivated by these challenges, which have at least demonstrated that our understanding of the MBL regime is still rather incomplete.…”
Section: Mbl Regimementioning
confidence: 94%
“…We also note that recently there have been a number of papers expressing various levels of skepticism about the stability of the MBL phase in the limits of large systems and long times [44][45][46][47][48][49], and a number of challenges to those conclusions [50][51][52][53]. While our results do not support (nor directly contradict) any of these arguments against the existence of the MBL phase, our work was, in part, motivated by these challenges, which have at least demonstrated that our understanding of the MBL regime is still rather incomplete.…”
Section: Mbl Regimementioning
confidence: 94%
“…This makes understanding of ergodic to MBL transition a formidable undertaking, especially in conjunction with non-perturbative mechanisms of delocalization of MBL phase [21][22][23]. Despite intensive research [20,[24][25][26][27][28][29][30][31][32][33][34][35][36] the status of the MBL phase is not fully understood as shown by the recent debate about the stability of MBL [37][38][39][40][41][42][43][44][45]. On the other hand, the existence of MBL is essentially certified in sufficiently strongly disordered spin chains as shown in [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of works have questioned the stability of the MBL phase [3][4][5][6][7][8]. In turn, some of the conclusions were challenged by follow up papers [9][10][11][12][13].…”
mentioning
confidence: 99%